The Impact of Employment Quotas on the Economic Lives of Disadvantaged Minorities in India - Nishith Prakash (Institute of Labor Economics (IZA), 2020)
India has the world's biggest and arguably most aggressive employment-based affirmative action policy for minorities. This paper exploits the institutional features of a federally mandated employment quota policy to examine its causal impact on the economic lives of the two distinct minority groups (Scheduled Castes and Scheduled Tribes). My main finding is that a 1-percentage point increase in the employment quota for Scheduled Castes increases the likelihood of obtaining a salaried job by 0.6-percentage points for male Scheduled Caste members residing in the rural sector. The employment quota policy has no impact for Scheduled Tribes. Contrary to popular notion, I do not find evidence of "elite-capture" among the Scheduled Castes â exteuro“ the impact is concentrated among members who have completed less than secondary education. Consistent with the employment results, I find that the policy improved the well-being of Scheduled Castes members in rural areas who have completed less than secondary education. Finally, the impact of the employment quota policy varies by state characteristics.
Keywords: H40; J21; J31; J45; O10; 330; consumption expenditure; Scheduled Tribes; Scheduled Castes; employment quota; public sector; India